2018
DOI: 10.1371/journal.pone.0206349
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical evaluation of hybrid double plate osteosynthesis using a locking plate and an inverted third tubular plate for the treatment of proximal humeral fractures

Abstract: BackgroundTreating proximal humerus fractures can be challenging because of large metaphyseal defects that conceal anatomical landmarks. In such cases, medial cortical support with, for example, calcar screws, is mandatory. Nevertheless, varus dislocations and implant failures in patients with impaired bone quality persist. Thus, the need for effective treatment of these patients exists. Hybrid double plate osteosynthesis was introduced as an alternative, yielding similar results as calcar screws. However, a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 32 publications
0
17
0
2
Order By: Relevance
“…The advantages of this hardware include affordability, low profile, better adaptation to the surface, and the ability to place screws at various angles in order to avoid contact with the screws from the lateral locking plate, which have a fixed angle. Theopold et al also demonstrated that the use of a second plate alters load distribution [5]. In their experiment, they used an inverted non-locked one-third tubular plate in the bicipital groove.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The advantages of this hardware include affordability, low profile, better adaptation to the surface, and the ability to place screws at various angles in order to avoid contact with the screws from the lateral locking plate, which have a fixed angle. Theopold et al also demonstrated that the use of a second plate alters load distribution [5]. In their experiment, they used an inverted non-locked one-third tubular plate in the bicipital groove.…”
Section: Discussionmentioning
confidence: 99%
“…Varus reduction and insufficient bone stock contribute to the high number of cases in which surgery is unsuccessful [1]. Recently several authors have called attention to the lack of medial support as an important risk factor for surgical failure [25]. Krappinger et al indicated age >63 years, bone mineral density levels <95 mg/cm 3 , non-anatomic reduction, and failure to restore cortical medical support as risk factors for post-osteosynthesis failure [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations